ANALISIS YURIDIS OPTIMALISASI PENDAPATAN DESA MELALUI PROGRAM PAMSIMAS - Hariadi, Dadang Budi; Zamroni, M (Program Pascasarjana Universitas Sunan Giri Surabaya, 2018)
The purpose of this study was to determine the important role of the utilization of clean water in meeting the needs of the community through the PAMSIMAS program that is able to support life in carrying out development in the present and in the future. In the problems faced by the number of villages that received the PAMSIMAS program assistance currently showing unpreparedness in the management of the program, the expected PAMSIMAS program was far from the expected benefits of the community in using clean water. In this study to examine more on the problems that arise, researchers use normative research supported by an empirical approach. From the research, the researchers found indicators of problems that were the constraints of the ineffectiveness of a government program to meet the needs of the community, which among others, the absence of special assistance from the government regarding the mechanism in the program. The duration of responsive embodiment of regulatory instruments issued from 2008 to 2018..